1998
DOI: 10.1007/s003830050334
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal follow-up of pulmonary function after lobectomy in childhood - factors affecting lung growth

Abstract: We examined the changes in pulmonary function values in 27 patients who underwent a lobectomy due to cystic lung disease and compared the results regarding such factors as disease type, age at operation, and preoperative infections. Percent vital capacity (%VC) decreased immediately after lobectomy, but recovered to normal values within 2 postoperative years and remained within or above the normal range. The ratio of residual volume to total lung capacity (RV/TLC) rose temporally with the increase in %VC, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 4 publications
1
41
1
1
Order By: Relevance
“…Ayed and Al-Rowayeh [17] reported no significant changes in spirometric pattern comparing pre-and post-operative spirometries in 14 [18]. In our series, abnormal spirometric patterns were more common than in the above mentioned and were unrelated to the length of follow-up.…”
Section: Discussioncontrasting
confidence: 62%
“…Ayed and Al-Rowayeh [17] reported no significant changes in spirometric pattern comparing pre-and post-operative spirometries in 14 [18]. In our series, abnormal spirometric patterns were more common than in the above mentioned and were unrelated to the length of follow-up.…”
Section: Discussioncontrasting
confidence: 62%
“…This is corroborated by a study in children aged 1 month-11 yrs who underwent lung lobectomy due to pulmonary cystic disease [42]. Pulmonary function analysis performed over two post-operative years indicated that complete normalisation of pulmonary function can be achieved in children aged ,4 yrs at the time of operation.…”
Section: Discussionmentioning
confidence: 60%
“…In naphthaleneinduced injury, selective loss of nonciliated bronchiolar cells occurs without apparent injury to or proliferation of alveolar epithelial cells, whereas in the pneumonectomy model marked hyperplasia and proliferation occurs in both airways and alveoli, involving multiple epithelial and nonepithelial cell types (25,26). Nevertheless, dynamic changes in the same transcription factors were associated with regeneration of the bronchiolar epithelium after both naphthalene injury and pneumonectomy models.…”
Section: Discussionmentioning
confidence: 99%
“…Compensatory lung growth occurs in conducting airways as well as lung parenchyma following unilateral pneumonectomy (25,26). We determined whether the regrowth of bronchiolar epithelium was associated with similar changes in transcription proteins that were observed in ciliated cells during repair after naphthalene injury.…”
Section: Expression Of Sox17 and Sox2 In The Squamous Cells Lining Thmentioning
confidence: 99%